Reform proposal for marriage taxation in Germany: De facto income splitting with a low transferable amount - Stefan Bach; Björn Fischer; Peter Haan; Katharina Wrohlich (DIW Weekly Report, 2020)
Two traditional options for reforming Ehegattensplitting, the joint taxation of married couples with full income splitting, are de facto income splitting (Realsplitting) or individual taxation with a transferable personal allowance. However, these proposals do not significantly reduce the marginal tax burden on the secondary earner's income and therefore only minimally encourage married women to participate in the labor market. Another option for reform is an additional personal allowance for married couples, but this concept is difficult to understand and further benefits dual income couples with middle and high incomes. Moreover, alternative methods of taxing married couples in Germany must adhere to specific legal regulations. A satisfactory compromise would thus be de facto income splitting for married couples with a transferable amount equal to the personal allowance. This proposal fulfills the legal criteria, is easily understandable, generates a certain amount of additional tax revenue, avoids burdening the lower and middle income brackets, and encourages secondary earners to participate in the labor market.
Keywords: H24; J22; D13; D31; 330; family taxation; tax reform; female labor supply; income distribution